The Role of Human Resource Risk on Employee Performance in The Hybrid Workforce Era - Putri, Thasya; Syafitri, Utami Dyah; Sukmawati, Anggraini (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The COVID-19 pandemic has brought about significant changes, particularly in work systems and patterns. The adoption of a hybrid work model allows employees to work remotely based on individually or collectively negotiated work arrangements. However, implementing a hybrid workforce presents several challenges, such as communication issues, varying levels of technological proficiency among employees, irregular working hours, and the potential for internal team problems. By implementing a hybrid work system in Pegadaian Co., employees are exposed to risks from both financial and non-financial aspects. This study aims to identify employee characteristics and analyze the impact of the hybrid workforce era and human resource risks on employee performance. The research uses the descriptive analysis method and SEM-PLS. The results show that the hybrid workforce era has a positive effect on employee performance, demonstrating that employees feel more productive when working in the office. These findings suggest that Pegadaian Co. should provide a comfortable and practical office environment to facilitate employee performance. Conversely, the study finds that human resource risks do not significantly influence employee performance. The selection process is identified as a minor factor within the HR risk variable. The company's selection process prioritizes effectiveness and efficiency by focusing on recruitment needs and objectives. Keywords: flexible working arrangement, hybrid workforce, working from office, Pegadaian, employee performance